“Não é só saber fazer cerveja” : narrativas de artesanato e autenticidade na formação do mercado de cerveja artesanal no Brasil - Sgorla, Andrey Felipe (2021)
Based on a survey carried out between 2017 and 2020, this thesis aims at investigating the craft beer market development in Brazil. Through an ethnographic approach and participant observation, it has been searched to explore how narratives about craftsmanship and authenticity by microbrewery owners are used as a market device that contribute to legitimizing their products, obtaining recognition within the market, and building consumer relations in the context of the new spirit of capitalism. All around the world, the craft beer market has grown exponentially in recent years, with the opening of microbreweries and diversification of beer production. In most cases found in literature, and in my field, brewers have reported that brewing at home has been fundamental in driving career change. The growth of craft beer market has been introduced in a charming context with handmade products and foods, which provides an attraction to the consumer that involves a high degree of autonomy, passion, and work as a hobby in small businesses, where they use “intuitive knowledge”, as well as time flexibility to make craft beers. Besides, handcrafted products have been associated with identity markers to ensure their “authenticity”, meaning they are exceptional, and they attract interest for their economic and cultural ranges. The product enrichment work is not just a useful marketing strategy, nor is it just a process in which storytellers have added value to the product. So, craft production has, in fact, a tendency towards experienced individual notoriety, and individuals have been encouraged to search pleasure in the scope of work, where value is increasingly perceived in terms of identity and lifestyle rather than monetary terms. Thus, the main conclusions of this thesis indicate that practices and stories have been market devices used to highlight the handmade character of craft beer production, its authenticity, identity, recognition and location. Therefore, it can suit to justify the higher prices of craft beers compared to industrial ones, as the consumer is having a unique and remarkable experience.